Release of acetazolamide from swellable hydroxypropylmethylcellulose matrix tablets - (:unkn) unknown (MARCEL DEKKER INC, 1997)
Controlled-release swellable tablets were prepared by a simple direct compression process using hydroxypropylmethylcellulose (HPMC) as the matrix former. The effects of the viscosity and concentration of the polymer and the pH of the dissolution medium on the release behavior of acetazolamide were investigated. The influence of the drug particle size was also evaluated. Ten, 15, 20, and 25% of two different viscosity grades of HPMC were dry mixed with acetazolamide, Fast Flo Lactose, and magnesium stearate, then directly compressed into tablets. The experimental tablets were tested for their drug contents, weight variations, and hardnesses. Dissolution tests were carried out under sink conditions at three different pH values: pH 1.2, 5.4, and 7.4. Release rate data were evaluated according to the equation log M-t/M-infinity = log k + n log t.